An eco-feminist reading of Mahasweta Devi :A Review - Deepshikha (Innovative Research Thoughts, 2024)
Dissent is a way of life for a few. Mahasweta, an adorable, hardworking, as well as an energetic enthusiast, academician, reporter and productive author is one among those few who register their dissent at every given opportunity. In our country she becomes famous in the form of literary personalities. She becomes a writer who has published more than 100 books. Most of her works have been originally written in Bengali. Later on, her work takes the form of other languages like English. The stark realities and systemic injustice around her paved way to become a writer – activist. Her involvement in the People‟s Theatre movement of Bengal, the wake of Naxalite movement of the 1950‟s and the first hand experience of the life and struggles of tribals in Bihar, West Bengal, Madhya Pradesh and Chhattisgarh shaped her life and career. Major part of her journalistic writings describe the “police atrocities, failures in the implementation of government programmes, exploitation of sharecroppers and miners, unemployment and landlessness, environmental degradation, and the need to protect and foster tribal languages and identity”.